2017
DOI: 10.1007/s00423-017-1596-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of parastomal hernia in the emergency setting

Abstract: Use of a resorbable synthetic mesh during emergency ostomy formation showed no significant preventive effect on formation of parastomal hernia after 1 year. Although surgery was often conducted in a severely contaminated field, the procedure was without significantly increased complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…48 One study has looked at the efficacy of prophylactic mesh use in the emergency setting and did not identify a significant preventative effect on parastomal hernia formation after 1 year. 49 There remains limited data on the long-term cost effectiveness of prophylactic mesh use.…”
Section: Parastomal Herniamentioning
confidence: 99%
“…48 One study has looked at the efficacy of prophylactic mesh use in the emergency setting and did not identify a significant preventative effect on parastomal hernia formation after 1 year. 49 There remains limited data on the long-term cost effectiveness of prophylactic mesh use.…”
Section: Parastomal Herniamentioning
confidence: 99%
“…There was no correlation between infection-related events and hernia recurrence [43]. In other areas such as emergency stoma creation Lykke et al found that the insertion of absorbable mesh, even in the presence of contamination, was not associated with increased complications [44]. It appears that permanent synthetic or biosynthetic mesh can now be used in clean-contaminated and contaminated fields.…”
Section: What About In Contamination?mentioning
confidence: 99%
“…Several randomized control trials (RCTs) and meta-analyses have shown positive results for synthetic meshes utilized as prophylaxis with various techniques and meshes [5, 6, 1219]. Trials have demonstrated a lower incidence of PSHs without a higher risk of complications.…”
Section: Introductionmentioning
confidence: 99%